Capital-Energy Substitution and Shifts in Factor Demand: A Meta-Analysis - Mark J. Koetse; Henri L.F. de Groot; Raymond J.G.M. Florax (Tinbergen Institute, 2006)
This paper presents results of a meta-regression analysis on empirical estimates of capital-energy substitution. Theoretically it is clear that a distinction should be made between Morishima substitution elasticities and cross-price elasticities. The former represent purely technical substitution possibilities while the latter include an income effect and therefore represent economic substitution potential. We estimate a meta-regression model with separate coefficients for the two elasticity samples. Our findings suggest that primary model assumptions on returns to scale, technological change and separability of input factors matter for the outcome of a primary study. Aggregation of variables and the type of data used in empirical research are also relevant sources of systematic effect-size variation. Taking these factors into consideration, we compute ideal-typical elasticities for the short, medium and long run. The resulting figures clearly show that s! ubstitution elasticities are substantially higher than cross price elasticities. Therefore, despite considerable technical opportunities for capital-energy substitution, they are almost entirely outweighed by the negative income effect brought about by energy price increases; the short and medium run cross price elasticities are not statistically different from zero. In the long run this pattern does not hold. Our findings therefore suggest that actual changes in the demand for capital due to energy price increases take time.
Keywords: C10; D24; D33; E23; O33; Q40; 330; production function; capital-energy substitution; cross-price elasticity; Morishima substitution elasticity; meta-analysis